The Effect of Nitrogen Gas Flushing on Intermediate Products Formation in Acidogenic Stage of Anaerobic Process of Cocoa Sweatings - Syafila, Mindriany; Handajani, Marisa; Prayascitra, Adearty (ITB Journal Publisher, LPPM ITB, 2010)
Cocoa is one of Indonesian-main plantation commodities. During the cocoa seed drying process, there are two types of waste that are cocoa pod and cocoa sweating. Since the organic compounds contained in cocoa sweating is high enough, it is possible to anaerobically treat this wastewater in order to recover either intermediate or end products. Preliminary study showed that the existence of H2 in the reactor would block acetic acid formation. Therefore, the aim of this current experiment was to decrease hydrogen partial pressure by flushing various nitrogen gas flow rate to shift the intermediate products during the cocoa sweating anaerobic treatment. The experiments were carried on a Circulating Bed Reactor (CBR) which contained organic compounds around 100,000 mg/l COD. Then, the reactor was flushed continuously with nitrogen gas as without flushing, 125 ml/min, 500 ml/min and 750 ml/min. The results show there was a possibility that the introduction of nitrogen gas into the reactor could shift the profile of the intermediate product formation. At lower nitrogen gas flow rate more ethanol was formed than acetate formation, although at higher nitrogen gas flow rate the formation of acetate was still low enough.Â